2020
DOI: 10.1103/physrevmaterials.4.056008
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic hierarchical micro/nano texturing of TiAlV alloys by femtosecond laser processing for the control of cell adhesion and migration

Abstract: https://repositorio.uam.es Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…[15] Thus, it can be concluded that hierarchical textures with different-sized features have proven to be useful for further enhancing the functionality of surfaces compared with singlescale patterns. [16,17] Pulsed laser sources with pulse durations in the nanosecond and picosecond regime are frequently used to create such textures in the micrometer range. Most research on surface functionalization has been conducted on polished surfaces with significant lower roughness values.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Thus, it can be concluded that hierarchical textures with different-sized features have proven to be useful for further enhancing the functionality of surfaces compared with singlescale patterns. [16,17] Pulsed laser sources with pulse durations in the nanosecond and picosecond regime are frequently used to create such textures in the micrometer range. Most research on surface functionalization has been conducted on polished surfaces with significant lower roughness values.…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond laser surface modifications on titanium and alloys substrates have been proved as a feasible tool to improve cells adhesion, differentiation, proliferation, and all together, more effectively boost osseointegration of the implant. In general, this physical modification technique allows: (1) custom design of nano-and micro-structures, such as laser induced periodically surface structure (LIPSS), ripples, columns, pits, and spikes [21][22][23], with an appropriate selection of laser beam parameters and conditions [24][25][26][27]; (2) formation of roughness with enhancement of wettability [28,29] or hydrophilicity-hydrophobicity of treated surfaces [29,30]; (3) inducing protein adsorption and following localized adhesion formation and cell shape-based mechanical restraints that promote osteogenic differentiation and hence, superior osseointegration of implants [31,32]; (4) prevention of bacterial adhesion and biofilm formation [33,34]; (5) variation of chemical composition of laser modified surfaces, for instance, bone-like apatite precipitation [35,36] and formation of nano-or micro-layers of oxides [37] such as, for example, protective TiO 2 on titanium substrates.…”
Section: Introductionmentioning
confidence: 99%
“…These methods usually require multiple steps to complete the fabrication of HMs, and the process is complex, time‐consuming, and expensive, which limits the rapid fabrication and applications of flexible piezoresistive sensors. By contrast, laser has the advantages of fast and high efficiency for maskless, [ 29–32 ] making it a promising method for fabricating flexible electronics. [ 33 ] Deka et al.…”
Section: Introductionmentioning
confidence: 99%
“…[1] At present, researchers have proposed various manufacturing methods for developing flexible limits the rapid fabrication and applications of flexible piezoresistive sensors. By contrast, laser has the advantages of fast and high efficiency for maskless, [29][30][31][32] making it a promising method for fabricating flexible electronics. [33] Deka et al [34] induced carbon nanostructures on the carbon fabric using a continuous wave laser, which was subsequently used in fabricating a flexible strain sensor.…”
Section: Introductionmentioning
confidence: 99%